«Corrupt» or «efficient»? The normalization of the improper use of fuel in the police organization of Lima - Villaorduña, José Manuel (2019)
This paper examines cases of illicit fuel use on the part of members of the Peruvian National Police (PNP) in Lima, by regarding the phenomenon as part of the generalized and normalized corruption within the institution. This approach accounts for the failure of the implemented oversight systems to regulate fuel usage and the persistence of irregular practices, such as fuel extraction and unauthorized vehicle use given that these practices have their origin in and in turn uphold structural deficiencies and cultural characteristics of the institution. This research provides an account of the characteristics and mechanisms that allow the generalization of corruption, highlighting those activities that legitimize said practices among members’ narratives. As a result, a positive appraise of illicit fuel use has been constructed in relation to an apparent fulfillment of the institutional mission. Following this approach, traditional definitions of corruption in the public sector and their consequences are problematized here. Information examined in this paper comes from the Direction of Logistics of the PNP (DIRLOG) and from testimonies collected during interviews with members of the organization.